PREFERENSI MAKAN KUMBANG KOKSI (Epilachna admirabilis) PADA BEBERAPA TANAMAN SAYURAN FAMILI SOLANACEAE - Bagus Suyoga, Kompyang; Watiniasih, Ni Luh; Suartini, Ni Made (SIMBIOSIS, 2016)
Plant cultivation has been commonly practiced, particularly vegetable plants, such as eggplant, tomato and chili. However, many problems are persisted that is the pest attack. Epilachna admirabilis (Coleoptera) is one pest that commonly attack vegetable plants. Many techniques have been applied to avoid this pest, but the result has not been in satisfantion. This study aimed to investigate the feeding preference of E. admirabilis, hence, the timing of eradication of this pests will be understood. This study was conducted in the Ecology Laboratory, Department of Biology, Mathematic and Natural Science Faculty, Udayana University on three different vegetable leaves, namely: the leaves of eggplant, tomato and chili. The results showed that, based on the time of arrival and leaf consumed on each type of plant leaves, E. admirabilis chose the leaves of eggplant and tomato first compared to chili. Epilachna admirabilis tend to consume the leaves of eggplants compared to tomato, and there was no chili leaves has been consumed by this beetles. Keywords: eggplant, tomato, chili, pest, Epilachna admirabilis
Keywords: eggplant, tomato, chili, pest, Epilachna admirabilis